Legal Responsibility in Handling Medical Cases: Assessing Health Insurance Policies in Indonesia - Ardilla, Ninda Mulya Ike; Susilowati, Indah (PT. Anagata Sembagi Education, 2025)
The increase in medical dispute cases in Indonesia reflects the disparity between patient expectations of health services and the standards applied by medical personnel. The main factors causing disputes include medical negligence, lack of informed consent, and limited transparency in the treatment process. Regulations such as Law No. 29 of 2004 on Medical Practice and Law No. 36 of 2009 on Health have regulated the responsibilities of medical personnel, but their implementation still faces challenges. On the other hand, national health insurance schemes such as BPJS Kesehatan also face obstacles in ensuring a balance of legal protection for patients and medical personnel. The INA-CBGs payment system often does not reflect the complexity of medical cases, thus impacting the quality of health services. The inconsistency of regulations between Law No. 40 of 2014 on Insurance and Law No. 36 of 2009 on Health also causes legal uncertainty in the resolution of medical disputes. This study uses normative juridical methods with legislative, conceptual, and case approaches to analyze related regulations and legal practices. The results of the study show the need for policy reforms that balance economic efficiency and legal protection. With the strengthening of regulations, transparency, and fairer dispute resolution mechanisms, it is hoped that the health law system in Indonesia can run more effectively and fairly.